Physical Bean Quality of Arabica Coffee (Coffea Arabica) Cultivated at High and Medium Altitude - Dwi Nugroho; Panjisakti Basunanda; Suryadi Mw (Indonesian Coffee and Cocoa Research Institute, 2016)
Reducing productivity, outbreak of insects and diseases, and decreasingin physical and cup quality are major problems for Arabica coffee cultivation inmedium altitude. The aim of this study was to investigate the effect of altitude onphysical quality in eight genotypes of Arabica coffee. This research was conductedat two locations i.e. Andungsari Research Station-Bondowoso (1250 m asl. ashigh altitude) and Kalibendo Estate-Banyuwangi (700 m asl. as medium altitude).Randomized complete block design was used with three replications. Collecteddata consisted of outturn, weight of 100 beans, shape bean normality, apparentswelling, bulk density before and after roasting. Combined analysis on the physicalquality traits of green bean showed genotype x altitude interactions on weight of100 beans, percentage of normal beans and percentage of empty bean. Altitudesignificantly influenced coffee outturn. Decreasing in altitude from 1.250 m asl.to 700 m asl. caused declining in the outturn as much 32.9%. BP 700A, K 29, K34, K 79, and K 99 were genotypes that stable to produce normal bean and emptybeans at high and medium altidute, while K 8, K 130, and SIG were genotypeswith high normal beans at high altitude but not stable. Genotype x altitude interactiondid not occur for physical quality of other variables of outturn, bulk densitybefore and after roasting, apparent swelling, percentage of round beans,percentage of elephant beans, and percentage of triage beans. Altitude showedsignificant effect on all of physical quality of bean variables.